FAKTOR-FAKTOR PENGHAMBAT PENANGANAN KERAWANAN PANGAN (FOOD INSECURITY) OLEH FOOD AND AGRICULTURE ORGANIZATION (FAO) DI SUDAN SELATAN PADA 2014-2017 - Dian Melati Sukma; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The aim of this research is to describe food insecurity, explaining Food and Agriculture Organization (FAO), dan to find out inhibiting factors for handling food insecurity by FAO in South Sudan.The perspective used by researcher in this study is pluralism which states that non-state actor is one of actors in international relations and author also used theory of international organization. The level of analysis is group behaviour that is group behaviour became a main focus of this research. The method used by researcher to exmine this research is by qualitative method, where research conduct research through books, official web and journals concerned with the research.The result of this study is the inhibiting factors for handling food insecurity by FAO in south Sudan 2014-2017 are conflict and violence, poor infrastructure, high inflation, and climate change.Keyword: Food insecurity, FAO, IPC, South Sudan